Procedural learning and school-age language outcomes in children with and without a history of late talking - Kautto Anna; Mainela-Arnold Elina (WILEY, 2025)
Background
'Late talkers' (LTs) are toddlers with late language emergence that cannot be explained by other impairments. It is difficult to predict which of these children continue to present long-term restrictions in language abilities and will later be identified as having a developmental language disorder. Procedural memory weaknesses have been suggested to underlie developmental language disorders, but have not been investigated in LTs.
Aims
We investigated the relationships between aspects of procedural memory and school-age language abilities in children with and without a history of LT. We hypothesized that children with a history of LT exhibit (1) restrictions in procedural memory when compared with children with typical early development (TED); and (2) a positive association between procedural memory and school-age language abilities.
Methods & Procedures
We recruited 79 children (7;5-10;5), 43 of whom had a history of LT. Aspects of procedural memory, procedural learning and motor planning were assessed using the serial reaction time and the end-state comfort tasks. School-age language abilities were measured using standardized tests.
Outcomes & Results
Counter to expectations, motor planning was not associated with a history of LT or school-age language abilities, and the children with TED did not show stronger procedural learning as compared with peers with a history of LT. However, weaker school-age language abilities were associated with weak procedural learning in TED group.
Conclusions & Implications
Factors other than deficits in procedural memory are likely to underlie LT. Procedural learning shows promise as a potential predictor of language development in children that are not identified as LTs.
What this paper adds
What is already known on the subject
Poor procedural learning has been associated with developmental language disorders and suggested to underlie language difficulties. However, to our knowledge, this study is the first to investigate procedural learning and its associations with language outcomes in LTs.
What this paper adds to existing knowledge
Consistent with prior research, we found an association between language abilities and procedural learning in school-aged children, but found no evidence for poor procedural learning in children with a history of LT. Furthermore, the school-age language outcomes were only associated with procedural learning in children with no history of LT.
What are the potential or actual clinical implications of this work?
Our findings suggest that factors other than limitations in procedural learning underlie LT. However, procedural learning could be a useful predictor for school-aged language outcomes in children not identified as LTs.